The Influence of Digital Transformation on Sustainable Performance Through Innovation: A Literature Review - Rahayu, Sucik (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
An important contributing aspect to the dynamic shifts in the contemporary business environment is digital transformation, involves implementing significant adjustments to business processes and offering clients additional value via the use of cutting-edge technologies like big data, artificial intelligence, and the Internet of Things. Examining how digital transformation affects corporate sustainability and innovation performance is the goal of this study, which also focuses on how innovation functions as a mediator in this relationship. Sustainable performance, which includes consideration of environmental and social impacts, has become increasingly important in today’s business strategies, requiring companies to consider sustainability aspects in every operational aspect of the company. involves implementing significant adjustments to business processes and offering clients additional value via the use of cutting-edge technologies like big data, artificial intelligence, and the Internet of Things. The objective of this study is to examine how digital transformation affects corporate sustainability and innovation performance, with a focus on innovation’s function as a mediator in this relationship. These findings provide in-depth insight into the complex relationships and energetic causality between digital technology, innovation, performance, and sustainability, and provide strategic guidance for companies in developing sustainable policies and practices in the ever-evolving digital era.